2019
DOI: 10.3892/mmr.2019.10611
|View full text |Cite
|
Sign up to set email alerts
|

miR‑497 inhibits the proliferation and migration of A549 non‑small‑cell lung cancer cells by targeting FGFR1

Abstract: Fibroblast growth factor receptor 1 (FGFr1) signaling has been reported to contribute to the carcinogenic progression of various cancer types. Previous studies have demonstrated that FGFr1 expression is increased in non-small cell lung cancer (nSclc) and promotes cancer cell metastasis. However, the molecular mechanisms underlying increased FGFr1 expression in nSclc remains largely unknown. in the current study, microrna (mir)-497 levels were observed to be inversely correlated with FGFr1 expression in tumor s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 37 publications
3
6
0
Order By: Relevance
“…The present study explored the expression of miR‐338 in the NSCLC. We demonstrated that the miR‐338 level was also down‐regulated in NSCLC tissues when compared with the adjacent normal tissues, which was consistent with previous results (Zhang, Shao, et al, ; Zhang, Ding, et al, ). In addition, the level of miR‐338 was also down‐regulated in NSCLC cell lines.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The present study explored the expression of miR‐338 in the NSCLC. We demonstrated that the miR‐338 level was also down‐regulated in NSCLC tissues when compared with the adjacent normal tissues, which was consistent with previous results (Zhang, Shao, et al, ; Zhang, Ding, et al, ). In addition, the level of miR‐338 was also down‐regulated in NSCLC cell lines.…”
Section: Discussionsupporting
confidence: 92%
“…Lung cancer, one of the most frequently diagnosed cancers, leads to the largest number of cancer‐related deaths worldwide (Zhang, Shao, Lin, Liu, & Yang, ; Zhang, Ding, & Zhang, ). According to the recent data, we know that the 5‐year survival rate of patients with lung cancer is only 15%.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pre-treatment with MAPK inhibitors reduced the protein expression of Bax promoted by IL-1α in the MC3T3-E1 cells, suggesting that the signi cance of JNK and the p38 MAPK signaling in modulating IL-1α-induced apoptosis and osteoblast differentiation of MC3T3-E1 cells [23]. The negative correlation between miR-497 and the JNK signaling has been highlighted in non-small cell lung cancer [24].…”
Section: Discussionmentioning
confidence: 96%
“…27 Moreover, Huang et al suggested that miR-497 could act as a tumor suppressor in NSCLC to hinder the proliferation and migration of NSCLC cells. 28 For miR-25-3p, Ding et al reported that miR-25 could promote the migration and invasion of NSCLC. 20 Also, Xiang et al suggested that miR-25 was related to the proliferation and motility of NSCLC.…”
Section: Discussionmentioning
confidence: 99%